A year of foot and ankle orthotic provision for adults: prospective consultations data, with patient satisfaction survey. - Malkin, K; Dawson, J; Harris, R; Parfett, G; Horwood, P; Morris, C; Lavis, G (2008)
OBJECTIVES: To characterise 12 months' adult, foot and ankle orthotic out-patient consultations in a regional centre; and to survey patients regarding their satisfaction with services received. METHODS: Prospective survey questionnaires completed by: (1) orthotists, during consecutive clinic consultations (n=4402 representing 2494 patients); (2) all patients receiving foot or ankle orthoses (n=1469), mailed 5 weeks later. Questions included a standard foot pain item, patients' perceived usefulness of the orthosis, and satisfaction with services received. Logistic regression identified factors associated with patients finding their orthosis 'very' or 'fairly helpful'. RESULTS: Consultations addressed myriad foot, ankle or other conditions. EVA (soft) foot orthoses were most commonly prescribed. The response rate from patients was 72%. Most (73%) said their orthosis would be 'very' or 'fairly helpful'. Following adjustment, females were less likely than males to find orthoses helpful (OR 0.71, p=0.031). All older age groups were at least twice as likely to find orthoses helpful as patients aged <40 (p<0.01). Ninety percent of respondents were 'very' or 'fairly satisfied' with the service received. CONCLUSIONS: Women, younger patients and those with more severe pain were less likely to perceive benefit from foot and ankle orthoses than other groups and may therefore require adjuvant or alternative intervention.